Gravitational interactions of binary systems in the massive planetesimal disc - Lopez, Maria Cristina (2024)
The prevalence of binary systems within our Solar system has become a common phenomenon, with over 500 systems identified. However, the connection that exists between the different dynamic mechanisms that give rise to their intricate orbital structure and the durability of these systems over time continues to be the subject of intense research. Encouraged by several works indicating that the number of binaries would have been much greater at the beginning of the outer Solar system, in our study we delve into the dynamical evolution of binary objects within the primordial populations of the massive disc of planetesimals between 15 and 30 au. By concentrating specifically on gravitational disturbances caused by neighbouring bodies, the research aims to investigate the effects on orbital dynamics resulting from the presence of binary objects to different extents within the studied populations. The results of our experiments indicate that populations with different binary fractions would not engender significantly divergent changes in the orbits of the study objects after 100 Myr of evolution. The survival of these systems, only considering a scenario of encounters and collisions between neighbours, would not have occurred in large quantities, being even lower in the outermost regions of the disc (25–30 au).